2014
DOI: 10.1063/1.4895936
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of strong local ferroelectric ordering in a thermoelectric semiconductor

Abstract: It is thought that the proposed new family of multi-functional materials namely the ferroelectric thermoelectrics may exhibit enhanced functionalities due to the coupling of the thermoelectric parameters with ferroelectric polarization in solids. Therefore, the ferroelectric thermoelectrics are expected to be of immense technological and fundamental significance. As a first step towards this direction, it is most important to identify the existing high performance thermoelectric materials exhibiting ferroelect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…[1][2][3][4][5][6] Within the AgSbSe 2 structure, Ag and Sb are generally assumed to randomly occupy the Na sites of the NaCl-type lattice, [7][8][9][10] which is consistent with ab initio calculations showing the total energies of the various ordered structures to be very close, thus allowing the presence of a significant density of disorder defects and mixed phases. A careful structural characterization has shown domains of ordering, not only in AgSbSe 2 , 11 but also in the related AgSbTe 2 , 12 correlating well with calculations showing a rhombohedral ordering to be the most energetically favorable in AgSbSe 2 . 13 Atomic ordering within the AgSbSe 2 crystal has a significant impact on the electronic structure near the band gap, which dominates the electronic properties 14 and provides the material with ferroelectric properties.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Within the AgSbSe 2 structure, Ag and Sb are generally assumed to randomly occupy the Na sites of the NaCl-type lattice, [7][8][9][10] which is consistent with ab initio calculations showing the total energies of the various ordered structures to be very close, thus allowing the presence of a significant density of disorder defects and mixed phases. A careful structural characterization has shown domains of ordering, not only in AgSbSe 2 , 11 but also in the related AgSbTe 2 , 12 correlating well with calculations showing a rhombohedral ordering to be the most energetically favorable in AgSbSe 2 . 13 Atomic ordering within the AgSbSe 2 crystal has a significant impact on the electronic structure near the band gap, which dominates the electronic properties 14 and provides the material with ferroelectric properties.…”
Section: Introductionsupporting
confidence: 77%
“…13 Atomic ordering within the AgSbSe 2 crystal has a significant impact on the electronic structure near the band gap, which dominates the electronic properties 14 and provides the material with ferroelectric properties. 11 AgSbSe 2 is a narrow, indirect band-gap semiconductor (0.03-0.10 eV) showing p-type conductivity. 15 However, an apparent optical bandgap of 0.6-1.1 eV 2, [15][16][17][18] and a high optical absorption coefficient (10 4 cm À1 ) have also motivated the use of AgSbSe 2 for photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ram Seshadri and Nicola A. Hill reported that ferroelectricity and highly distorted monoclinic structure in BiMnO 3 arises due to lone pair activity 25 . Lone pair driven ferroelectricity/antiferroelectricity were also observed in other materials -AgSbSe 2 , BiAlO 3 , Pb 2 MgWO 6 [49][50][51] . In a recent study, pair distribution function (PDF) analysis revealed that stereo-chemical activity of the 6s 2 lone pair produces signicant lattice anharmonicity and local distortion in AgBiS 2 while on average the system showed cubic Fm-3m structure 52 .…”
Section: Resultssupporting
confidence: 57%
“…Recently, the I–V–VI 2 (where I = Cu, Ag, or alkali metal; V = Sb, Bi; VI = S, Se, Te) class of compounds gained significant attention because of their potential applications in thermoelectrics, phase-change memory devices, , and solar cells . Some of the members in I–V–VI 2 (for example, AgSbSe 2 , AgSbTe 2 , NaBiTe 2 , NaBiSe 2 , NaSbSe 2 , and NaSbTe 2 ) crystallize in cation disordered rock salt structure and others such as AgBiS 2 , AgBiSe 2 , and AgBiTe 2 exhibit exotic structural phase transitions as a function of the temperature. The presence of a stereochemically active ns 2 lone pair on group V (Sb/Bi) elements and a disordered cation sublattice resulted in highly anharmonic bonding associated with soft phonon modes and low phonon group velocity in I–V–VI 2 compounds. , The ultralow thermal conductivity and tunable electronic structure made them appropriate for thermoelectric power generation. ,, Although the cubic I–V–VI 2 compound crystallizes in cation disordered structure, Mahanti and co-workers predicted several plausible low-energy ordered structures using theoretical calculations .…”
Section: Introductionmentioning
confidence: 99%